Study of creatinine transport through chitosan/pectin/poly(vinyl alcohol) blend membranes - Ni Putu Sri Ayuni; Ni Wayan Yuningrat (Indonesian Journal of Biotechnology, 2016)
Creatinine was final product of creatine metabolism inskeletal muscle. Increasing of creatinine showed decreasing of kidney function. Kidney fuction decreased could be treated by hemodialysis (HD). One of the natural polymer was cellulose which often used as hemodialysis membrane. Chitosan as natural membrane was used as membrane in this research because the structure was almost similar to cellulose. Chitosan was complexed by pectin and poly(vinil alcohol) (PVA) to fixed mechanical characteristic of membrane. The objective of this research were to synthesize, characterize, and know efficiency of creatinine transport using chitosan/pectin/PVA blend membranes. The functional groups of synthesized membrane were characterized by FTIR spectrophotometer. Efficiency of optimum creatinine transport was known by using membrane with chitosan and pectin ratio70:30 while PVA used 0.5%; 1.0% and 1.5%. The source and acceptor phase resulted were complexed by picric acid and analyzed by Ultraviolet-Visible (UV-Vis) Spectrophotometer. The result of membrane synthesized which was analyzed by FTIR Spectrophotometer shows that there is a band broadening on wave number 3448.72 cm-1. It is indicated that there are an overlapped stretching of hydrogen bond -OH on PVA and NH2 on chitosan. The optimum creatinine 70 ppm transported using membrane with 1.5% PVA addition is 59%.